Studies on Behaviour of Regular and Irregular Tall Structures Subjected to Earthquake Loading - G. M. Naveen; . Chaya (New Approaches in Engineering Research Vol. 7, 2021)
Multi storey buildings are constructed by Reinforced concrete are subjected to earthquake forces are affected dangerously, they get failure during earthquake. The main reason for this failure is that the irregularity in building structures. In this paper study is made to find the response of regular and irregular building structures having plan irregularity located in seismic zone V. In this present study Analysis has been made by taking 10 storey building by Response Spectrum Method using ETABS 2015 and code IS 1893:2002 (part 1). Analysis is carried out for Regular and Irregular buildings at a height of 35.5 m in zone V. Behavior of structures are comparing the responses in the form of maximum storey displacement, storey drift, storey stiffness, periods and frequencies of modes during earthquake. Presently there are four models. One is Regular structure and remaining are Irregular structural models, all models have different shape but having same area. An attempt is made to study the Response of building structures with respect to the loads and their combinations. The results comparison is made by taking maximum load combinations considering the primary loads (LL, DL, WL, and EQL). Totally four Configuration models are considered for the analysis.